Perkembangan dan Integrasi Hukum Islam dalam Sistem Hukum Nasional di Indonesia - Riski Febria Nurita; Djawahir Hejazziey (Bhirawa Law Journal, 2026)
This research examines the historical development and forms of integration of Islamic law within Indonesia’s national legal system in the framework of a pluralistic rule-of-law state. As a country with a plural legal system, Indonesia has experienced a long and complex dynamic in accommodating Islamic law, ranging from the era of Islamic kingdoms, the colonial period with restrictive legal policies, to the post-independence and reform eras, which have provided broader space for the application of sharia values. This study employs a normative legal research method using statutory, conceptual, historical, and philosophical approaches through library-based research analyzed qualitatively in a descriptive-analytical manner. The findings show that the integration of Islamic law into the national legal system is not merely formal-symbolic, but substantive in nature through the internalization of Islamic values within Pancasila and the Preamble of the 1945 Constitution, particularly the principles of divinity, justice, and humanity. Normatively, this integration is manifested in various legal products, such as family law, religious courts, Islamic economics, Islamic philanthropy, and special regional arrangements such as in Aceh. Furthermore, the development of Islamic law also indicates a transformation trend toward a maqasid al-shariah approach, strengthening Islamic economics, harmonization with international law, and adaptation to technological developments. Thus, Islamic law functions as one of the sources of values and materials in the development of Indonesia’s national legal system, while remaining consistent with the principles of the Pancasila state and legal pluralism.